+0  
 
0
249
1
avatar

(2x-1)^2=(x+1)^2

plssss help

Guest Jun 18, 2017
 #1
avatar+88899 
+1

(2x -1)^2  = ( x + 1)^2

 

4x^2 - 2x - 2x + 1  = x^2 + 2x + 1

 

4x^2  - 4x + 1  =  x^2 + 2x + 1

 

3x^2 - 6x  = 0

 

a =3 , b = -6,  c = 0

 

 

cool cool cool

CPhill  Jun 18, 2017

25 Online Users

avatar

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.